ABORTO - INCONSTITUCIONALIDADE E IMORALIDADE - Lazzarotto, Lorenzo Matheus Da Pieve; Lopes, Alexia Gabriela Camargo; Argerich, Eloisa Nair De Andrade; Perin, Luana Nascimento; Strücker, Bianca (Salão do Conhecimento, 2017)
Trabalho desenvolvido no transcorrer da disciplina de Direito Constitucional II